Mejoramiento genético en conejos para carne (Oryctolagus cuniculus) - Antonini de Ruiz, Alicia Graciela (2010)
The selection of lines has been the main strategy of genetic improvement in meat rabbits. The paternal lines are selected for average daily gain or weight to the age of slaughter, both related to the feed conversion index. For the maternal lines prevails like criterion of selection the litter size to the birth or upon weaning, and more recently indirect methods as the rate of ovulation. Intensive meat production in rabbits is based on a three way crossbreeding scheme. The first crossing includes two maternal lines generating females F1, a second crossing consists of the utilization of male of a third paternal line, the born individuals of this crossing are destined to slaughter. The estimation of genetic parameters for different populations has been object of study in different productive clusters in order to establish in each case the characteristics to include in the plans of improvement. The values of heritability observed by diverse authors for litter size are similar (0.05 to 0.14) while for the variables related to the weaning weight, the discrepancies among the authors are greater (0.03 to 0.72).